The Effect of the Zigzag Run Training Method on Players’ Dribbling Skills in the Futsal Extracurricular Program at MTSN 01 South Bengkulu - Roki Bimantoro; Azizatul Banat; Deffri Anggara (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of the Zig Zag Run training method on the dribbling skills of players in the futsal extracurricular program at MTSN 01 South Bengkulu. The research method used was an experimental design with a pre-test and post-test on the same group. This method was used to examine the effect of the Zig Zag Run training method on the dribbling skills of players in the futsal extracurricular program at MTSN 01 South Bengkulu. Based on the research, the results showed that, according to the pre-test and post-test measurements using a group t-test statistical approach, the calculated t-value for the overall training method was 5.292 and the critical t-value (α = 0.05) was 1.729, which means the calculated t-value is greater than the critical t-value. Therefore, it can be concluded that there is a significant effect of the Zig -Zag Run training method on the dribbling skills of futsal players at MTSN 01 South Bengkulu. In other words, the proposed research hypothesis has been significantly validated. As previously discussed in the theoretical review, the Zig-Zag Run training method is effective in improving dribbling skills in futsal.